LANDASAN PERNIKAHAN MENURUT SíŠRAT Wí‰DHí… TANí…Yí… - Hartanto, Doni Dwi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2020)
(Title: The Marriage Archetype Pivoting To Síªrat Wédhí¥ Taní¥yí¥). Marriage is one of the cycles of life conducted based on norms society, one of the example is marriage happening in Javanese society. The research entitled The Marriage Archetype Pivoting to Síªrat Wédhí¥ Taní¥yí¥ aimed to describe the marriage archetype in Javanese script. The method used to analyze in this research is qualitative-descriptive by using the script entitled Síªrat Wédhí¥ Taní¥yí¥ which belong to the library of Dewantara Kirti Griya in Yogyakarta. The data were gathered by translating, reducing, and categorizing the text. The data analysis was analysed heuritically and hermeneutically. Based on the discussion, there are some obtained data abaout marriage in Javanese background, those are: 1) partner characterization; 2) man obligation in marriage; 3) the marriage archetype; 4) the marriage manners. The rule or etiquette conveyed in this script is expected to be one of the pivoting principles to select the marriage partner, and it also becomes a way of consideration in doing the prospective partner selection in marriage. By referring those tenets, expectedly marriage relationship will be long-lasting and bring forth happiness and welfare. Keywords: archetype, marriage, Javanese, Síªrat Wédhí¥ Taní¥yí¥